PARADOKS IMPLEMENTASI EKONOMI ISLAM DI NEGARA-NEGARA MUSLIM: INTEGRASI NILAI TAWAKKAL DAN IKHTIAR - Nasution, Asmita Mardiana; Sari, Cici Prawita; Siregar, Putri Handayani; Lubis, Delima Sari (Indonesian Scientific Journal of Islamic Finance, 2025)
The Islamic economic system is widely promoted in Muslim-majority countries as a comprehensive alternative to capitalism and socialism. However, its practical implementation often reveals a paradox: while Islamic values such as tawakkal (trust in God) and ikhtiar (human effort) are central to the theology of Islamic economics, they are rarely embedded in institutional and policy frameworks. This study aims to explore this paradox by analyzing the integration of tawakkal and ikhtiar within the economic governance structures of Muslim countries. Drawing on a qualitative literature review, the research identifies key obstacles including weak institutional capacity, low public literacy, and a symbolic adoption of Islamic financial instruments. The theoretical foundation is based on maqāṣid al-sharīʿah, which supports a balance between spiritual trust and rational action. The findings reveal that Islamic economic policies remain largely cosmetic, lacking systemic mechanisms to actualize these spiritual-economic values. Moreover, the integration of tawakkal and ikhtiar has not been adequately addressed in fiscal or monetary policy design. This study contributes a conceptual framework for rethinking Islamic economic policy with authentic value integration and highlights the urgent need for institutional reform, policy alignment, and educational strategies that embed ethical-spiritual dimensions into economic development.